Metabolic Modifications, Inflammation, and Cancer Immunotherapy - Zheng, Sihao; Song, Qibin; Zhang, Pingfeng (Frontiers in Oncology, 2021)
Cancer immunotherapy has accomplished significant progresses on treatment of various cancers in the past decade; however, recent studies revealed more and more heterogeneity in tumor microenvironment which cause unneglectable therapy resistance. A central phenomenon in tumor malignancy is metabolic dysfunctionality; it reprograms metabolic homeostasis in tumor and stromal cells thus affecting metabolic modifications on specific proteins. These posttranslational modifications include glycosylation and palmitoylation, which usually alter the protein localization, stability, and function. Many of these proteins participate in acute or chronic inflammation and play critical roles in tumorigenesis and progression. Therefore, targeting these metabolic modifications in immune checkpoints and inflammation provides an attractive therapeutic strategy for certain cancers. In this review, we summarize the recent progresses on metabolic modifications in this field, focus on the mechanisms on how glycosylation and palmitoylation regulate innate immune and inflammation, and we further discuss designing new immunotherapy targeting metabolic modifications. We aim to improve immunotherapy or targeted-therapy response and achieve more accurate individual therapy.